Medical Emergencies in Pediatric Dentistry - Dubravka NEGOVETIĆ VRANIĆ; Josipa Jurković; Jesenka Jeličić; Antonija Balenović; Gordana Stipančić; Ivana Čuković-Bagić (University of Zagreb. School of Dental Medicine, 2016)
Medical emergencies that are life threatening can occur in dental practice. Complications may arise because of an underlying disease or a reaction to medication. Reactions to medications may be allergic and toxic. The most common reactions are toxic reactions to local anesthetics, whereas allergies occur mainly as a consequence of the application of antibiotics, usually penicillin. In response to stress, vasovagal syncope typically occurs. Other causes may be related to an underlying diseasespecific pathology (such as acute asthma attack, diabetic ketoacidosis, hypoglycemia, or seizures) or accidents (aspiration of a foreign body causing obstruction of the respiratory system). For all the above conditions, guidelines have been established that need to be known. If complications occur or necessary measures are not taken, it can lead to cardiac and respiratory arrest. Therefore, cardiopulmonary resuscitation is needed. All procedures and dosages should be adapted to the age of the child.